Empirical Studies: Upaya Masyarakat Desa Penagan Dalam Mendorong Percepatan Pembangunan, Efisiensi Pelayanan Publik Melalui Pemekaran Desa - Virna Dewi; Sri Yuliana (Justici, 2021)
The issue of the expansion of Penagan Village isn’t a new issue in the community. The villagers of Penagan have been trying very hard to penagan Village expansion. But, there are no result for their efforts. The villagers of Penagan are still waiting for government to respond their demand. The villagers of Penagan claimed that they dont understand the reasons why government never response their demand. This research is a normative research and to make the analysis more deeper, this research used explanatory research. The research data collected from document analysis such as statute, doctrine, observations, interviews and questionnaires with the villagers of Penagan. The result of this research shows that Penagan Village is worhty for expansion. Village expansion will be able to give a good effect like better development and efficiency of public services. Village Expansion also hoped to solve problem that come because of a big teritorial and population. So, that the future of the village can be more advanced.